2020
DOI: 10.1021/acsabm.0c00216
|View full text |Cite
|
Sign up to set email alerts
|

Localization of Coated Iron Oxide (Fe3O4) Nanoparticles on Tomato Seeds and Their Effects on Growth

Abstract: Enlighten -Research publications by members of the University of Glasgow http://eprints.gla.ac.uk Localization of Coated Iron Oxide (Fe 3 O 4 ) Nanoparticles on Tomato Seeds and their Effects on Growth

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 30 publications
(80 reference statements)
2
10
0
Order By: Relevance
“…Earlier studies reported increase in seed germination, plantbiomass, seedling growth/vigor and yield after application of iron oxide nanoparticles [70][71][72][73][74]. Treatment of tomato seeds with Fe 3 O 4 nanoparticles had no side effects on plant growth and development [75]. Similarly, our results veri ed the previous research by observing the enhancement in growth parameters of tomato plants treated with various concentrations of IONPs.…”
Section: Impact Of Ionps On Tomato Growth-parameterssupporting
confidence: 89%
“…Earlier studies reported increase in seed germination, plantbiomass, seedling growth/vigor and yield after application of iron oxide nanoparticles [70][71][72][73][74]. Treatment of tomato seeds with Fe 3 O 4 nanoparticles had no side effects on plant growth and development [75]. Similarly, our results veri ed the previous research by observing the enhancement in growth parameters of tomato plants treated with various concentrations of IONPs.…”
Section: Impact Of Ionps On Tomato Growth-parameterssupporting
confidence: 89%
“…Earlier studies have reported an increase in seed germination, plant biomass, seedling growth, and yield after the application of IONPs [ 70 74 ]. Treatment of tomato seeds with Fe 3 O 4 NPs has no side effects on plant growth and development [ 75 ]. Similarly, our results verified the previous research by observing the enhancement in growth parameters of tomato plants treated with various concentrations of IONPs.…”
Section: Resultsmentioning
confidence: 99%
“…Bands at 1651 and 1632 cm −1 corresponded to stretching of the amide CO bond, 47 while a sharp band at 1400 cm −1 could be attributed to the stretching of aromatic ring C−N or C−C bonds. 13,48 Bands at around 1055 cm −1 were characteristic of stretching of C−O bonds of alcohols, esters, or ethers.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Bands at 1651 and 1632 cm –1 corresponded to stretching of the amide CO bond, while a sharp band at 1400 cm –1 could be attributed to the stretching of aromatic ring C–N or C–C bonds. , Bands at around 1055 cm –1 were characteristic of stretching of C–O bonds of alcohols, esters, or ethers. , The presence of these groups in the spectra for both the filtrate and the nanoparticles indicated the presence of these organic groups on the surfaces of the nanoparticles, possibly in the form of a capping on the iron oxide matrix.…”
Section: Resultsmentioning
confidence: 99%